Treatment of human scabies with oral ivermectin - Ismael A. CONTI DÍAZ; Jorge AMARO (Revista do Instituto de Medicina Tropical de São Paulo, 1999)
Thirty-eight patients with scabies (21 males and 17 females) received oral ivermectin in two doses of 200 mg/kg at 7 days interval. Excellent results were achieved in 29 cases (76.34%), improvement in 6 (15.78%) and poor responses in 3 (7.88%). Tolerance was satisfactory-excellent in 32 patients (84.2%). The effectiveness and safety of the drug described in previous studies are confirmed by the present results.